Vietnam as if... Tales of youth, love and destiny - Huynh, Kim (ANU Press, 2015)
Vietnam as if... follows five young people who have moved from the countryside to the city. Their dramatic everyday lives illuminate some of the most pressing issues in Vietnam today: 'The Sticky Rice Seller' explores gender roles; 'The Ball Boy' is all about the struggles of sexual and ethnic minorities; 'The Professional' examines relations between rich and poor; 'The Goalkeeper' delves into politics and ideology; and 'The Student' reflects upon family and faith. The stories also reboot several classics of Vietnamese literature for the twenty-first century, including 'Floating Dumplings' by feminist poet Ho Xuan Huong, Vu Trong Phung's satire of French colonialism Dumb Luck, Nguyen Du's epic account of fate and sacrifice 'The Tale of Kieu', and the proclamations of Ho Chi Minh. These novellas reveal the deepest sentiments of Vietnamese youth as they - like youth everywhere - come of age, fall in love and contest their destiny. In 2011 Kim Huynh returned to Vietnam, having left more than three decades earlier. He had few plans other than to experience as much of his birthplace as possible. That year he came into contact with a wide range of people and took on many trades. Kim drank and dined with government officials, went on pilgrimages with corporate tycoons and marched in the streets against foreign aggression. He sold sticky rice, was a tennis player and also a ball boy, attended all manner of rituals and celebrations, eavesdropped on people in cafés and restaurants, and went back to the classroom as both a student and a teacher. Rich in detail and broad in scope, these tales capture Kim's experiences and imaginings of Vietnam as if....